A Wittgenstenian Language Games on Idealism and Realism: Lesson Learned for STEM Based Curriculum in Universitas Terbuka - Sukmayadi, Dodi (International Journal of Research in STEM Education, 2020)
This paper is to expound some note on philosophy in terms of contrast between idealism and realism in its various shades of grey. Included is its shade in (certain) Islamic perspective. The methods of analysis is that of Wittgenstenian language games (WLG) which proceed from several well-known statements or examples to dense possible meaning of them. The WLG is considered fruitful for the purpose of grounding theory and practice science-technology-engineering-math (STEM) based curriculum development and implementation. The subject matter discussed is how idealism and realism is expressed in the three three-generations of philosopher Socrates-Plato-Aristotle (SPA), Schopenhauer-Nietszsche-Foucault (SNF) and Hegel-Marx-Habermas (HMH). After mentioning an Islamic expression on idealism and realism as contrast of jabariyatism and mutazilitism, then it is time to see if Universitas Terbuka (UT) specifically and all (Indonesia) educational establishments in general have some lesson learned from that note on philosophy. In UT, in line mostly with Islamic expressions, idealism and realism is seen as contrast of content-based vs competency-based approach to curriculum development and implementation.